Implementasi Smart Mobility Sebagai Model Pembangunan Berkelanjutan di Daerah Khusus Ibukota Jakarta - Cherish Young; Felicia Evelyn; Dwi Putra Nugraha (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
This research aims to analyze the implementation of Smart Mobility as one of the key indicators of the Jakarta Smart City program to support sustainable development in the Province of DKI Jakarta. The study focuses on the application of Transit Oriented Development (TOD) and the operation of TransJakarta Electric Buses as concrete efforts to address traffic congestion and air pollution, which are major urban challenges. The research method employed is an empirical qualitative approach, relying on primary data obtained through interviews with relevant parties, as well as secondary data derived from legislation, official government documents, and academic literature. The research findings indicate that the development of TOD areas significantly contributes to improving public access to mass transportation and reducing dependence on private vehicles. Meanwhile, the use of TransJakarta Electric Buses represents an environmentally friendly transportation innovation that supports carbon emission reduction in DKI Jakarta, although it still faces obstacles in terms of fleet availability and investment. The implementation of this policy has shown positive impacts on shifting public behavior, as reflected in the increase of public transportation users from 18.86% in 2023 to 22.19% in 2024. However, there is still no definitive measurement of how much the policy has contributed to reducing air pollution levels. Therefore, periodic and comprehensive evaluations supported by accurate data are essential to ensure that this policy runs effectively and aligns with sustainable development goals. To realize a more environmentally friendly, sustainable and livable DKI Jakarta, collaboration between the government, private sector and the community is needed.